PENYIDIKAN TINDAK PIDANA PENIPUAN YANG DILAKUKAN OLEH CALO UMRAH DI KEPOLISIAN RESOR KOTA PEKANBARU - Sugianto, Tri Dayanto; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The travel organisers of travel umrah help people to travel to the holy land , behind this all the men who are responsible for profits that look for opportunities to commit fraud by means of the congregation of candidates . Fraud conducted by a pander umrah it includes a criminal act. It is associated with fraud criminal investigation conducted by brokers umrah police resort city in pekanbaru. The purpose of writing this thesis , videlicet; first , criminal investigation tindank fraud conducted by a pander umrah police resort city in pekanbaru , second , obstacles suffered by the investigation of criminal acts of fraud against conducted by ticket scalpers in pekanbaru police resort city , third , the efforts made in overcoming obstacles that have emerged in handle investigation of crimes carried out by a pander umrah police resort city in pekanbaru .The kind of research can be grouped in the kind of research this sociological , because in this research directly writer did an experiment the treatment at the site in order to provide a complete and clear picture about the problem of the treatment. The study is done on the force resort city pekanbaru , while sample the population and constitute a whole related parties due to the matter investigated in this study , a source of the data used , the primary data , tertier and secondary data , data collection techniques in the research by kuisioner , interview and study literature available . From the research problems there are three basic it can be concluded. The first is investigation the criminal act of fraud conducted by a pander umrah on the force resort city pekanbaru implemented according to the a legal statute the event of criminal. Second, obstacles faced criminal investigation against fraud committed by brokers umrah police resort city in pekanbaru rapporteur, namely a lack of evidence witnesses placed on it it said the distribution of duty and inter-unit satreskrim suspect has fled. Third, the efforts made in overcoming obstacles that have emerged in handle investigation of criminal acts of fraud conducted by a pander umrah on the force resort city pekanbaru is to do gave them knowledge and the information on the list of travel which has permission as the umrah worship , clarify a division of labor among the units on the force resort city pekanbaru , and to spend to catch the suspect who escaped. The authors suggestion, first, crime fraud investigation conducted by Police in umrah touts Resort City of Kekanbaru more effectively with duties and authority. Second, Barriers experienced against the crime fraud investigation conducted by Police in the resort of umrah touts Pekanbaru must be solved properly. The third , the efforts made in dealing with obstacles which arise in the criminal investigation of fraud by brokers umrah police resort in pekanbaru can finish .Keyword : Investigation â Criminal Act â Calo â Umrah.